2022
DOI: 10.1021/acs.jpca.2c06467
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Reactivities of Methanol and Methanediol in the Photolysis of Aqueous Nitrite Solution

Abstract: Ultraviolet irradiation of aqueous nitrite (NO2 –) quickly generates hydroxyl (OH) and nitric oxide (NO) radicals, which are subsequently consumed concomitantly with the generation of N x O y species. Recently, dissolved formaldehyde (CH2O) in aqueous solution (e.g., methanediol, CH2(OH)2), has been regarded as the precursor in the formation of atmospheric formic acid (HCOOH) via the reaction with OH and cascading processes (Nature2021593233237). In this work, a step-scan Fourier transform interferometer was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Small organic molecules such as humic acid and ethanol further consume the OH radical, causing the net depletion of nitrite upon ultraviolet treatment [104]. Recently, we studied the photolysis of nitrite (NO 2 À ) in the presence of methanol, ethanol [58], and methanediol (CH 2 (OH) 2 ) [59,105], which is the hydrated form of formaldehyde [106], to differentiate their reactivities in terms of the lengths of the hydrocarbons, the mono-ol, and diol. We found that the photolysis of neat NO 2 À leads to the generation of [107], an upper-bound bimolecular rate coefficient of methanol and ethanol with NO can be determined [58].…”
Section: Reactions In Aqueous Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Small organic molecules such as humic acid and ethanol further consume the OH radical, causing the net depletion of nitrite upon ultraviolet treatment [104]. Recently, we studied the photolysis of nitrite (NO 2 À ) in the presence of methanol, ethanol [58], and methanediol (CH 2 (OH) 2 ) [59,105], which is the hydrated form of formaldehyde [106], to differentiate their reactivities in terms of the lengths of the hydrocarbons, the mono-ol, and diol. We found that the photolysis of neat NO 2 À leads to the generation of [107], an upper-bound bimolecular rate coefficient of methanol and ethanol with NO can be determined [58].…”
Section: Reactions In Aqueous Solutionsmentioning
confidence: 99%
“…Accounting for the bimolecular rate coefficients of OH with CH 3 OH and C 2 H 5 OH and the transient population of N 2 O 3 [107], an upper‐bound bimolecular rate coefficient of methanol and ethanol with NO can be determined [58]. In addition, the reactivity of the simplest geminal diol, CH 2 (OH) 2 , which can be prepared by dissolving paraformaldehyde in water [108], was also compared with that of methanol [59]. The previous reports revealed that the bimolecular rate coefficients of OH with CH 3 OH and CH 2 (OH) 2 are similar [107, 109].…”
Section: Applications In Absorptionmentioning
confidence: 99%
See 1 more Smart Citation